PRACTICAL ASPECTS OF THE ACTIVITIES OF NEO-BANKS IN A HIGH-TECH FINANCIAL ENVIRONMENT (Вісник: Міжнародні відносини, 2024)
The article defines the general trends in the development of neobanks. It was established that the level of penetration of online banking in European countries ranges from 15% to 96% (Norway, Denmark, Sweden, Finland). The beginning of the development of neobanking and the set of innovative banking institutions operating exclusively on the Internet have been determined. An analysis of the practical aspects of the activities of neobanks in a highly technological financial environment was carried out on the example of the case of Dukascopy Bank. It has been established that the digital model of neobanks is the basis for ensuring stability in such an environment. In addition, digital models and technological solutions ensure profitability and positive financial results in the short term. Mobile retail banking provides virtual banks with stable development and growth. A private cryptocurrency made possible by technological solutions, an additional product for customer acquisition and income diversification.
Keywords: online banking, neobanks, technological solutions of neobanks, virtual banks, mobile banking